Current Perspectives in Human Papillomavirus - Saxena, Shailendra K. (Infectious Diseases, 2019)
This book gives a comprehensive overview of recent advances in human papillomavirus (HPV) infection, as well as general concepts of infections, immunopathology, diagnosis, treatment, epidemiology, and etiology. It examines current clinical recommendations in the management of HPV, highlighting the ongoing issues, recent advances, and future directions in diagnostic approaches and therapeutic strategies. The book focuses on various aspects and properties of HPV, whose deep understanding is very important for safeguarding the human race from further loss of resources and economies due to HPV infection. I hope that this work will increase the interest in this field of research and that the readers will find it useful for their investigations, management, and clinical usage.